تحليل الإشارة الشخصية (Deiksis Persona) في حكاية الحديث الثالث من كتاب مواعظ العصفورية - Saidah, Siti Saidatul Fitriah Lailatul Badriah; Rohanda, Rohanda; Rosalita, Rosalita (Lughaat: Journal of Arabic Linguistics, 2025)
The study of language, commonly referred to as linguistics, encompasses various subfields, one of which is pragmatics. Within pragmatics, there are further areas of study, including deixis. Deixis is an essential aspect often used in both oral and written communication, such as in hikayat (classical Malay literary works). Hikayat is a type of written literary work widely read for its moral lessons, including in the Hikayat Hadis Ketiga from the book al-Mawa'izh al-Ushfuriyah. This study aims to identify the forms and contextual meanings of personal deixis in the Hikayat Hadis Ketiga of the book al-Mawa'izh al-Ushfuriyah. The research method employed is descriptive analysis with a qualitative approach. The data consists of personal deixis found in the Hikayat Hadis Ketiga. Data collection was carried out using the listening and note-taking techniques. The data analysis process involved reading, identifying, categorizing, analyzing, and concluding. The results of this study indicate that the Hikayat Hadits Ketiga from al-Mawa'izh al-Ushfuriyah predominantly uses third-person deixis compared to first and second-person deixis. The most frequently used third-person deixis includes dlomir bariz muttashil (ه) and dlomir moustatir jawaz (هو), which mostly refer to Ali Ra. and the Prophet Muhammad Saw.